TINDAKAN SOSIAL MASYARAKAT YANG TINGGAL DI AREA PEMAKAMAN UMUM SUNGAI PANAS KOTA BATAM - Ardheny Wisnu Wardana; Sri Wahyuni; Rahma Syafitri (LPPM STISIP Persada Bunda, 2023)
This study aims to find out how social actions are carried out by people living in the hot river public cemetery area of Batam city. In this study using qualitative methods with a descriptive method approach, the data obtained through the results of observations, interviews and documentation in this study to determine the informants needed through purposive sampling techniques first determine the criteria for informants based on the results of this research analysis looking at the causes of people choosing to live in public cemetery areas. Researchers also found actions taken by people living in the public cemetery area, including selling, using social assistance, and volunteering. This condition is meant by Max Weber in instrumental rationality actions, affective rationality actions, value rationality actions and traditional rationality actions in which a person performs rational actions to obtain the goals he wants to achieve and also the actions taken are determined by conscious beliefs in the form of ethical, aesthetic and religious values. Individuals perform actions hereditaryly and emotionally.